Facile preparation of multi-scale nanoarchitectures on cotton fabric with low surface energy for high performance self-cleaning. Issue 11 (1st November 2020) - Tian, Shengnan; Zhao, Jian; He, Jiahuan; Shi, Haiting; Jin, Bingqi; Qin, Shuang; Xia, Yanling; Xiao, Changfa
Abstract: Self-cleaning cotton fabric with excellent amphiphobicity was fabricated by building micro-nanostructures with low surface energy on cotton fabric surface. TiO2 and SiO2 blend nanoparticles modified by hydrolytic (heptadecafluoro-1, 1, 2, 2-tetradecyl)trimethoxysilane (17-FAS) were co-deposited onto cotton fabric by two different coating methods: 1) suction filtration for immobilizing the modified TiO2 /SiO2 onto cotton fabric based on cellulose swollen action by N-methylmorpholine-N-oxide (NMMO) solution; 2) adhesion by spraying waterborne polyurethane (WPU) before coating. The performance of self-cleaning fabric was investigated by draping properties, air permeability, water-vapor transmission, tensile properties, abrasion resistance and washing fastness. The resultant self-cleaning fabric exhibited superhydrophobicity and excellent oleophobicity based on contact angles of 151.9° for water, 141.7° for liquid paraffin, 137.8° for epoxidized soybean oil and 133.1° for diesel oil, respectively. WPU method possessed better washing fastness and could keep high amphiphobic effect. WPU method is considered as a reliable and facile solution to amphiphobic fabric, showing great promise for industrial-scale respect in self-cleaning textiles. Graphical Abstract: